Systemic effects of surgical intervention on disease activity, daily function, and medication in patients with rheumatoid arthritis. (2nd September 2016) - Iwata, T; Ito, H; Furu, M; Hashimoto, M; Fujii, T; Ishikawa, M; Azukizawa, M; Hamamoto, Y; Mimori, T; Akiyama, H; Matsuda, S
Abstract : Objectives : Although tight control of rheumatoid arthritis (RA) has been achieved through the development of effective medication, surgical intervention is still required for a certain subpopulation of patients. To examine the systemic effects of orthopaedic surgery, we evaluated improvements in disease activity, daily function, and medication after surgery. Method : A prospective cohort study was conducted in 196 cases of elective orthopaedic surgery in 150 patients with RA from January 2011 to March 2014 in our institution. The 28-joint count Disease Activity Score based on erythrocyte sedimentation rate (DAS28-ESR) and modified Health Assessment Questionnaire (mHAQ) scores just before surgery and at 6 and 12 months after surgery were examined prospectively. Concomitant medications were also investigated. Results : Significant improvement was seen in the DAS28-ESR and mHAQ scores for replacement surgery in both the upper and lower extremities, and for arthroplasty/arthrodesis in the upper extremities at the 12-month follow-up. Partial mHAQ scores for the lower extremities were significantly reduced in lower replacement surgery, and partial mHAQ scores for the upper extremities were significantly reduced in upper arthroplasty/arthrodesis surgery. Although the use of conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) did not decrease after surgery, the dose of prednisolone (PSL) decreased significantly at 12 months after surgery, especially in the well-controlled group and in surgical procedures in the lower extremities. Conclusions : Elective orthopaedic surgery improves both systemic disease activity and general functional impairment. Orthopaedic surgery is effective in reducing the amount of medication required postoperatively.